Taking solution proton NMR to its extreme: prediction and detection of a hydride resonance in an intermediate-spin iron complex - Ott, Jonas C.; Wadepohl, Hubert; Enders, Markus; Gade, Lutz H. (Journal of the American Chemical Society, 2018)
Guided by DFT based modeling the chemical shift range of a hydride resonance in the proton nuclear magnetic resonance (NMR) spectrum of the intermediate-spin, square planar iron complex tBu(PNP)Fe-H was predicted and detected as a broad resonance at −3560 ppm (295 K) with a temperature dependent shift of approximately 2000 ppm between 223 and 383 K. The first detection of a metal-bonded hydrogen atom by solution NMR in a complex with a paramagnetic ground state illustrates the interplay of theory and experiment for the characterization of key components in paramagnetic base metal catalysis.
Gesehen am 12.03.2020